ANALISIS PENGETAHUAN PASCAKOLONIAL, PENGETAHUAN ADAT, DAN PEMBANGUNAN MANUSIA BERKELANJUTAN - Angella Denis (LENTERA: JOURNAL OF GENDER AND CHILDREN STUDIES, 2026)
This article aims to analyze the growth and thematic trends of research studies on postcolonial, indigenous, and sustainable development in Indonesia. The study used a bibliometric and material analysis approach using data obtained from the Scopus database. An in-depth examination was conducted on publications between 1992 and 2025. The research study used Title-Abs-Key (postcolonial AND Indonesia), and out of 370 articles accessed through a Bibliometric database, 100 articles were critically analysed. Study identified patterns in educational institutions, distribution of scientific disciplines within articles produced, and how productive scholars are in publishing articles related to postcolonial, indigenous knowledge and sustainable human development. The study also aimed at exploring various topics conducted by researchers, efforts to strengthen postcolonial, indigenous knowledge, and sustainable development. In addition, the research study examined the advancements in postcolonial perspectives, indigenous knowledge, and sustainable human development in Indonesia. The results contribute to understanding the strengths and weaknesses of these areas and their implications for the country. The findings will enable policy-makers to forge collaboration with educational institutions in developing educational policies and promote collaboration between Indonesia scholars and international scholars. Publication trend indicates that postcolonial research within educational institutions in Indonesia would double.